The controller-first constraint beyond the Basic Variety: how do instructed learner varieties solve contexts of competition? - Repiso Isabel (Linguistics)
The Basic Variety has been described as a fully fledged system that is developed in second-language acquisition. It is guided by a small number of interacting phrasal, semantic, and pragmatic constraints. This article is devoted to the semantic controller-first constraint, which says that “the NP-referent with highest control comes first” in discourse contexts where this constraint comes into conflict. The Basic Variety, as described by Klein and Perdue, relates to migrant learners that were exposed to target languages in naturalistic contexts and situations outside the classroom. Our study also deals with learners living in the target language’s country at the time of the data collection, but our learners were benefiting from foreign language teaching at university. The goal of this study is twofold. The first part of the article discusses the origins of the key notion of ‘controller’ and introduces related theoretical underpinnings, such as argument hierarchies of transitive verbs and crucial factors determining argument realization. Our analysis shows that the controller-first constraint overlaps with two key concepts of the description of L1 functional grammars – i.e., control asymmetry and the Actor-Undergoer Hierarchy – suggesting that it does not only pertain to the Basic Variety but broadly speaking to the human language capacity. The second part of this study presents some preliminary results on the L2 grammars of Spanish-speaking learners of French in a context of ‘competition’. Our results show the pervasiveness of the controller-first constraint on L2 grammars beyond initial, non-instructed learner varieties, suggesting that this semantic principle is not totally independent of (a) the specifics of the source language and (b) the target constructions of the foreign language classroom.